IMPLEMENTASI DAN IMPLIKASI UNDANG UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT TERHADAP KESEJAHTERAAN MASYARAKAT (Badan Amil Zakat Kota Bandar Lampung) - Nurasari, Nurasari; Mu'in, Fathul; Sulistyani, Ambar (ASAS, 2021)
Indonesia is a country with the largest Muslim population in the world. The large number of the Muslim population makes Indonesia has a large potential for zakat. Through zakat, it is hoped that Indonesia will be able to realize the country's goals. As stated in the preamble to the Constitution of the Republic of Indonesia, namely "advancing the welfare and the intellectual life of the nation". This type of research used in this research is qualitative research. Qualitative research is a research method based on the philosophy of postpositivism, used to examine the natural conditions of objects. This research is descriptive. Descriptive research is research that is intended to investigate conditions or other things that have been mentioned, the results of which are presented in the form of a research report. The implementation and implications of Law Number 23 Year 2011 in BASNAS Bandar Lampung City are carried out well. And BAZNAS Bandar Lampung City through funds obtained from zakat through several excellent programs such as the Healthy Bandar Lampung program, the Smart Bandar Lampung program, the Mandiri Bandar Lampung Program, the Bandar Lampung Care Program, the Bandar Lampung program, the Bandar Lampung Prosper and Justice.Keywords: Zakat, BAZNAS, Welfare, Bandar Lampung City